2021
DOI: 10.3889/oamjms.2021.6791
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrient Content and Total Lactic Acid Bacteria of Dadiah Pudding as Food Supplementation for Pregnant Women

Abstract: BACKGROUND: Dadiah, traditional yogurt from Indonesia, which is known as a source of probiotics, also contains micronutrients. AIM: This descriptive study aimed to determine whether additional ingredients and processes during the manufacture of Dadiah pudding maintain the iron, zinc, calcium, and total lactic acid bacteria (LAB) contents. METHODS: Dadiah pudding was made using Dadiah originated from Bukittinggi, West Sumatra. Micronutrient levels were analyzed according to Indonesian National Standard 01-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
4
0
1
Order By: Relevance
“…The pudding was cooled until 60-70 °C and then mixed well with dadih. Dadih pudding was poured into the pudding mold and chilled in the refrigerator for it to be ready to serve (Taufiqa et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pudding was cooled until 60-70 °C and then mixed well with dadih. Dadih pudding was poured into the pudding mold and chilled in the refrigerator for it to be ready to serve (Taufiqa et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…The result of a similar study found that total LAB in the original dadih (6.4 × 10 9 CFU/mL) was almost the same as those in Mango Dadiah (MD) pudding (6.1 × 10 9 CFU/mL), whereas they were reduced (2.4 × 10 9 CFU/mL) in Chocolate Dadiah (CD) pudding. A decrease of 62.5% of total LAB in CD as compared to the original dadiah may be due to the chocolate powder used as the additional ingredient in the pudding (Taufiqa et al, 2021).…”
Section: Lactic Acid Bacteria (Lab)mentioning
confidence: 99%
“…Dadiah adalah makanan tradisional Sumatera Barat yang dibuat dari susu kerbau yang di fermentasi alamiah dalam tabung bambu dan di tutup oleh daun pisang dan dibiarkan pada suhu kamar selama 2-3 hari. Dadiah telah banyak diteliti bahwa kandungan probiotik yang terdapat dalam dadiah jumlah nya tinggi sehingga jika di konsumsi dengan jumlah yang adekuat dapat meningkatkan kesehatan dan sistim imun (Taufiqa et al, 2021;Venema & Surono, 2019).Probiotik halal pada dadiah Lintau sudah di teliti dan di identifikasi memiliki kesamaan dengan L, fermentum. Dadiah yang mengandung probiotik ini akan dipakai sebagai starter dalam pembuatan produk Inovasi yogurt dari susu kambing Etawa yang merupakan salah satu unggulan produk susu murni di Padang Panjang.…”
Section: Pendahuluanunclassified
“…Vitamin C content can increase iron absorption (Rieny et al, 2021) and vitamin A affects iron metabolism, which can increase hemoglobin concentration (Jus'at et al, 2014)Additionally, dadih is a probiotic food source. In 100 g of dadih there are lactic acid bacteria 6,4x10 9 CFU/ml (Taufiqa et al, 2021). Previous studies demonstrated the ability of probiotics to increase iron absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Dadih contains essential minerals and vitamins that increase iron absorption ( Purnasari et al 2021). Iron in 100 g of dadih as much as 6,53 mg (Taufiqa et al, 2021). Iron plays a role in the formation of hemoglobin and transport of oxygen throughout the body (Wong, 2017).…”
Section: Introductionmentioning
confidence: 99%